Respon Imun Seluler Tikus Putih dengan Terapi Bakteriofag Rekombinan ϕSen-NF-Rec Penginfeksi Salmonella enterica - Hayatun Nafisah Ayu Qur'ana (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The global increase in antibiotic-resistant Salmonella enterica infections has raised serious concerns in both human and veterinary medicine. This situation has encouraged the development of alternative strategies to antibiotics, including the use of bacteriophages to control bacterial infections. This study aimed to determine the effect of recombinant bacteriophage ϕSen-NF-rec therapy on the cellular immune response in white mice infected with Salmonella enterica. A total of 24 white mice were divided into eight groups (three mice per group), including a control group, a Salmonella enterica infection group, and groups administered ϕWild-Type bacteriophages and recombinant bacteriophage ϕSen-NF-rec, as well as combinations with infection administered before or after bacterial challenge. Bacteria were administered orally, while bacteriophages were administered intraperitoneally. Serum samples were collected and analyzed for IFN-γ, IL-4, and IL-12 levels to evaluate the cellular immune response using a sandwich ELISA method. The administration of recombinant bacteriophage ϕSen-NF-rec in Salmonella enterica infected mice showed a significant effect on cellular immune parameters, as indicated by increased levels of IFN-γ and IL-12 and decreased levels of IL-4 compared to the control group. These findings suggest that recombinant bacteriophage ϕSen-NF-rec therapy is capable of shifting the immune response toward Th1 dominance while suppressing excessive Th2 activity, thereby potentially enhancing the effectiveness of the cellular immune response against Salmonella enterica infection.
FINALISASI oleh Arif 2026 Mei 19
Keywords: Bacteriophage therapy; Cytokines; Salmonella typhimurium; T cells